Analysis In Economic Law On The Consumer Lifestyle Of The Young Generation Who Failed To Pay Paylater - Banjarnahor, David; Banjarnahor, Daulat Nathanael (LPPM Universitas PGRI Sumatera Barat, 2023)
Currently, the phenomenon of using Paylater services in Indonesia, especially among the younger generation, has become a major highlight in recent months, although it offers convenience, there are significant risks, especially the occurrence of